Longitudinal assessment of diffusion-weighted imaging during magnetic resonance-guided radiotherapy in head and neck cancer - Simon Boeke; Jonas Habrich; Sarah Kübler; Jessica Boldt; Fritz Schick; Konstantin Nikolaou; Jens Kübler; Cihan Gani; Maximilian Niyazi; Daniel Zips; Daniela Thorwarth (Radiation Oncology)
Abstract Background For radiotherapy of head and neck cancer (HNC) magnetic resonance imaging (MRI) plays a pivotal role due to its high soft tissue contrast. Moreover, it offers the potential to acquire functional information through diffusion weighted imaging (DWI) with the potential to personalize treatment. The aim of this study was to acquire repetitive DWI during the course of online adaptive radiotherapy on an 1.5 T MR-linear accelerator (MR-Linac) for HNC patients and to investigate temporal changes of apparent diffusion coefficient (ADC) values of the tumor and subvolume levels. Methods 27 patients treated with curative RT on the 1.5 T MR-Linac with at least weekly DWI in treatment position were included into this prospective analysis and divided in four risk groups (HPV-status and localisation). Tumor and lymph node volumes (GTV-P/GTV-N) were delineated on b = 500 s/mm2 images while ADC maps were calculated using b = 150/200 and 500 s/mm2 images. Absolute and relative temporal changes of mean ADC values, tumor volumes and a high-risk subvolume (HRS) defined by low ADC tumor voxels (600 < ADC < 900 × 10−6 mm2/s) were analyzed. Relative changes of mean ADC values, tumor volumes and HRS were statistically tested using Wilcoxon-signed-rank test. Results Median pretreatment ADC value for all patients resulted in 1167 × 10−6 mm2/s for GTV-P and 1002 × 10−6 mm2/s for GTV-N while absolute pretreatment tumor volume yielded 9.1 cm3 for GTV-P and 6.0 cm3 for GTV-N, respectively. Pretreatment HRS volumes were 1.5 cm3 for GTV-P and 1.3 cm3 for GTV-P and GTV-N. Median ADC values increase during 35 fractions of RT was 49% for GTV-P and 24% for GTV-N during RT. Median tumor volume decrease was 68% and 52% for GTV-P and GTV-N with a median HRS decrease of 93% and 87%. Significant differences from 0 for mean ADC were observed starting from week 1, for tumor volumes from week 2 for GTV-P and week 1 for GTV-N and for HRS in week 1 for GTV-P and week 2 for GTV-N. Conclusion Longitudinal DWI acquisition in HNC is feasible on a MR-Linac during the course of online adaptive MR-guided radiotherapy. Changes in ADC and volumes can be assessed, but future work needs to explore the potential for biologically guided treatment individualization. Trial registration: NCT04172753, actual study start: 09.05.2018.